Colchicine suppression of corneal healing after strabismus surgery. Issue 7 (July 1977) - Biedner, B. Z.; Rothkoff, L.; Friedman, L.; Geltman, C.
Abstract : Two patients who had previously undergone uneventful operations for strabismus showed healing of corneal dellen and erosion after withdrawal of colchicine therapy. It is suggested that the exhibition of colchicine therapy for familial Mediterranean fever in these two cases was responsible for initial persistence of these two postoperative complications.